Epidemiology and seasonal patterns of hospitalized dengue cases in Muscat Governorate, Oman (2022–2023): A retrospective study - Ibtisam Khalifa Al-Maskari; Sanjay Jaju; Zainab M. Al-Zadjali; Amal Malehi; Asiya Al Hasni; Khaleefathullah A. Sheriff; Hilal Al Sidairi; Adil Said Al Wahaibi (PLoS ONE, 2026)
This study describes the epidemiological, clinical, and seasonal characteristics of hospitalized dengue fever (DF) cases in Muscat Governorate, Oman (2022–2023) and identifies factors associated with wet-season dengue occurrence. A retrospective analytical study was conducted using national dengue surveillance data of 345 laboratory-confirmed DF patients admitted to Sultan Qaboos University Hospital (SQUH) and the Royal Hospital (RH). Sociodemographic, clinical, and laboratory data were analyzed using descriptive statistics and logistic regression to identify factors independently associated with wet-season dengue cases. The results showed that of 345 patients, 54.8% were male, and 94.5% were Omani nationals. Most admissions occurred at RH (56.8%) and during the dry season (58.3%). Adults aged 41–60 years comprised the largest age group (44.6%). A distinct seasonal pattern was observed, with peaks in April-May of both years. Seeb Wilayat accounted for 69.3% of cases, followed by Bawshar (26.1%) (p = 0.027). Clinically, 84.6% had dengue with warning signs, while 15.4% developed severe dengue. Locally acquired infections represented 98.6% of cases. Hypertension (31.9%) and diabetes mellitus (25.2%) were the most common comorbidities. PCR positivity and hospital admission were more frequent during the wet season; however, these patterns are likely to reflect differences in testing and referral practices rather than increased dengue transmission. Overall, 96.2% of patients recovered, and 3.8% (n = 13) died. Multivariable analysis indicated that wet-season admissions were more likely to occur at SQUH (aOR = 1.72; 95% CI = 1.06–2.82; p = 0.030) and among PCR-confirmed cases (aOR = 1.38; 95% CI = 1.02–1.87; p = 0.040); these associations likely reflect hospital referral and diagnostic practices rather than increased transmission risk. In conclusion, hospitalized dengue cases in Muscat Governorate exhibited clear seasonal and geographic clustering, while associations with PCR positivity and hospital of admission reflect health-system and diagnostic patterns rather than increased dengue incidence. The predominance of locally acquired infections indicates ongoing endemic transmission. Strengthening vector surveillance, particularly in Seeb and Bawshar, and enhancing hospital preparedness prior to seasonal peaks remain important public health strategies, supported by existing literature rather than this study alone.